Improving Literacy Learning and School Library Management Through a Smart Literacy System for Kids at SDN Demaan (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Improving students' literacy skills is a key step toward achieving quality education. However, the implementation of literacy learning in elementary schools is not yet fully optimal, and the library's supporting resources have not been utilized effectively. As a result, students' literacy skills remain low. This situation is evident at SDN Demaan Jepara, which is a partner in this PKM activity. The aim of this PKM is to enhance teacher competency in developing student literacy skills and managing the library at SDN Demaan Jepara. The PKM activity employs a service-learning method, which includes stages of socialization, training, mentoring, and reflective evaluation of activities. It begins with an analysis of partner needs through observation and interviews. The targets of this PKM are the school principal, teachers, and education staff at SDN Demaan, totaling 20 participants. The results of this PKM show that the activity contributed to insights into differentiated literacy learning innovations, achieving a success rate of 90%. The program also positively impacted the skills of SDN Demaan Jepara teachers in using technology to enhance student literacy learning and in providing varied digital-based learning resources, with a success rate of 88%. Additionally, the 'Smart Literacy for Kids' application developed by the Service Team helps partners implement innovative literacy learning and effective library management, achieving a success rate of 88%. Therefore, this training and mentoring activity can positively affect the competency and creativity of the partners